Answer:
D.
Step-by-step explanation:
The mean is 11,000
Answer:
t=-4
Step-by-step explanation:
48/-12
Answer:
![\dfrac{x}{3}+\dfrac{3}{y}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%7D%7B3%7D%2B%5Cdfrac%7B3%7D%7By%7D)
Step-by-step explanation:
<u>Given fraction</u>:
![\dfrac{xy+9}{3y}](https://tex.z-dn.net/?f=%5Cdfrac%7Bxy%2B9%7D%7B3y%7D)
![\textsf{Apply the fraction rule} \quad \dfrac{a+b}{c}=\dfrac{a}{c}+\dfrac{b}{c}:](https://tex.z-dn.net/?f=%5Ctextsf%7BApply%20the%20fraction%20rule%7D%20%5Cquad%20%5Cdfrac%7Ba%2Bb%7D%7Bc%7D%3D%5Cdfrac%7Ba%7D%7Bc%7D%2B%5Cdfrac%7Bb%7D%7Bc%7D%3A)
![\implies \dfrac{xy}{3y}+\dfrac{9}{3y}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7Bxy%7D%7B3y%7D%2B%5Cdfrac%7B9%7D%7B3y%7D)
Rewrite 9 as 3 · 3:
![\implies \dfrac{xy}{3y}+\dfrac{3 \cdot 3}{3y}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7Bxy%7D%7B3y%7D%2B%5Cdfrac%7B3%20%5Ccdot%203%7D%7B3y%7D)
Cancel the common factor y in the first fraction and the common factor 3 in the second fraction:
![\implies \dfrac{x\diagup\!\!\!\!y}{3\diagup\!\!\!\!y}+\dfrac{\diagup\!\!\!\!3 \cdot 3}{\diagup\!\!\!\!3y}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7Bx%5Cdiagup%5C%21%5C%21%5C%21%5C%21y%7D%7B3%5Cdiagup%5C%21%5C%21%5C%21%5C%21y%7D%2B%5Cdfrac%7B%5Cdiagup%5C%21%5C%21%5C%21%5C%213%20%5Ccdot%203%7D%7B%5Cdiagup%5C%21%5C%21%5C%21%5C%213y%7D)
![\implies \dfrac{x}{3}+\dfrac{3}{y}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7Bx%7D%7B3%7D%2B%5Cdfrac%7B3%7D%7By%7D)
Answer:
hi im from another country see ya ... your country is amazing
Step-by-step explanation:
Answer:
1/5 and 2/10
Step-by-step explanation: